CSR Reporting and its Links to Financial Performance in Malaysia - Mr, Sukh Deve Singh (2004)
The overwhelming predominance of global trade in todays world greatly enhances the power vested in the hands of corporations, whilst with power comes responsibility and this power ought to be exercised with due care so that the risk of those with lesser power being harmed can be avoided and overall harmony exists. At the same time, corporations like Exxon Mobil, in the name of trade, campaign against the Kyoto Protocol which if implemented could lead to controls on hydrocarbon fuel usage (New Scientist, 2002; Godd and Lowen, 2001) and in Southeast Asia, large corporations like Asia Pulp and Paper were allowed to significantly damage the Indonesian rainforest (New Scientist, 2002).